A Molecular Secret Sharing Scheme. (30th November 2018) - Lustgarten, Omer; Carmieli, Raanan; Motiei, Leila; Margulies, David
Abstract: A method for implementing a secret sharing scheme at the molecular level is presented. By creating molecular code generators that are self‐assembled from several molecular components, we established a means for distributing distinct code‐activating elements among several participants. In this way, an authorization code can only be generated when all the participants are present, which ensures that highly secured systems cannot be operated by unauthorized individuals or disloyal users. Additional layers of protection result from the ability to program the security code by replacing one or several molecular components and by subjecting the system to distinct chemical inputs.